2022
DOI: 10.31253/te.v5i1.940
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Mint Leaf Types Based on the Image Using Euclidean Distance and K-Means Clustering with Shape and Texture Feature Extraction

Abstract: Mint is a plant that has many benefits and uses. However, some people are not familiar with the types of mint leaves because they cannot tell the difference. Actually, if you look closely, mint leaves have their own characteristic shape and texture. However, most people judge mint leaves to have a shape similar to other leaves so it is difficult to tell them apart. This paper aims to classify the types of mint leaves using the Euclidean distance algorithm and K-Means clustering with shape and texture feature e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…Another study for classifying mint leaves based on GLCM texture features using K-Means Clustering generated accuracy and sensitivity values of 83% and 82%, respectively [41]. Previous studies showed lower results because mint leaves have a higher feature closeness than CXR images in COVID-19 and normal cases.…”
Section: Measurement Indexmentioning
confidence: 99%
“…Another study for classifying mint leaves based on GLCM texture features using K-Means Clustering generated accuracy and sensitivity values of 83% and 82%, respectively [41]. Previous studies showed lower results because mint leaves have a higher feature closeness than CXR images in COVID-19 and normal cases.…”
Section: Measurement Indexmentioning
confidence: 99%
“…Their combined indices included precision (also known as producer accuracy), Recall (also known as user accuracy), F1-score (F 1 ), overall accuracy (OA), and kappa coefficient (Kappa), which were exploited to evaluate the final classification effectiveness. Precision, Recall, F1-score, OA, and Kappa are often utilized to calculate the accuracy of the classification [32,33], whose calculation formulas are as follows:…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Pendekatan yang dapat digunakan dalam penyelesaian klasifikasi citra yaitu euclidean distance. Pendekatan atau algoritma euclidean distance meruapakan sebuah pendekatan untuk mencocokan citra dengan melakukan identfikasi apakah citra tersebut memiliki kemiripan atau sejenis [8]. Cara kerja algoritma ini adalah *) penulis korespondensi: Farida Amalya Email: farida_a@staff.gunadarma.ac.id ISSN: 2477-5126 e-ISSN: 2548-9356 Farida Amalya: Klasifikasi Buah Berkhasiat Obat … 68 dengan melakukan pencarian terhadap kemiripan dua atau beberapa citra dengan memperimbangkan nilai jarak dari eucliedan, apabila jaraknya semakin dekat maka citra tersebut berada dalam satu kelas [9].…”
Section: Iunclassified